Genesis and Expansion of Brazilian Artistic Collectivism in the Early 2000s - Nogueira, Pedro Caetano Eboli (Farol, 2025)
This article analyzes the genesis and expansion of artistic collectivism in São Paulo in the early 2000s. We seek to understand how collaborative practices, artistic residencies, and activist actions, along with movements fighting for housing rights, shaped new relationships between art and politics. The research is based on documents, artists’ accounts, and critical bibliography. We demonstrate how the emerging collectivism established a field of aesthetic and social action that combines aesthetic experimentation and the struggle for rights.